1972
DOI: 10.1113/jphysiol.1972.sp010021
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of choline acetyltransferase activity in the carotid body of the cat

Abstract: 1. The distribution of choline acetyltransferase in the carotid body of the cat has been investigated with the electron microscope to determine sites of enzymic activity. This is of relevance to the possible role of acetylcholine as a transmitter in the carotid body. 2. Tissues were fixed for short periods and incubated by the method of Kasa, Mann & Hebb, for the fine structural localization of choline acetyltransferase. 3. The enzyme was found in the cytoplasm of the type I cells and seemed to be associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is worth noting here that these same authors have described the presence of P2Y 1 receptors on type I cells (924). In many ways, this hypothesis has a great number of similarities to earlier ones in which the type II cell was also ascribed a modulatory role in chemotransduction (52, 420, 663), but via type I cell derived ACh rather than ATP. Further studies may be warranted using models in which the type I and type II cells remain in natural contact with each other to establish the true functional role of the type II cell in chemotransduction.…”
Section: Cell Types Of the Carotid Bodymentioning
confidence: 60%
“…It is worth noting here that these same authors have described the presence of P2Y 1 receptors on type I cells (924). In many ways, this hypothesis has a great number of similarities to earlier ones in which the type II cell was also ascribed a modulatory role in chemotransduction (52, 420, 663), but via type I cell derived ACh rather than ATP. Further studies may be warranted using models in which the type I and type II cells remain in natural contact with each other to establish the true functional role of the type II cell in chemotransduction.…”
Section: Cell Types Of the Carotid Bodymentioning
confidence: 60%
“…In the ensuing decades, numerous studies investigated the role of ACh in chemosensation and demonstrated that small quantities of cholinergic agonists and antagonists profoundly altered chemoreceptor discharge 20. Neurochemical investigations indicated that the metabolic machinery necessary for ACh synthesis, storage and inactivation appear to be associated with type I cells in the carotid body 2,3,23,24,31,35,36 and that afferent fibers of the CSN are nearly devoid of cholinergic activity23, 28. In addition, it has been demonstrated that an ACh-like substance is released upon stimulation of the organ in vitrol7, Is.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the F.I.F. method, the chromaffine reaction of Hillarp and Hökfelt (in Pearse, 1972) (Kasa et al, 1970) or phospholine jodide (Burt, 1970) iso-Ompa was added to the medium (Ballard & Jones, 1972).…”
Section: Chapter I Introductionmentioning
confidence: 99%